1992
DOI: 10.1139/v92-240
|View full text |Cite
|
Sign up to set email alerts
|

Electronic configuration and structure of paramagnetic iron dinitrosyl complexes

Abstract: The electronic and geometric structures of paramagnetic iron dinitrosyl complexes have been investigated using electron spin resonance, infrared spectroscopy, and X-ray crystallography. It is concluded that these compounds are best described as 17 electron complexes with a d 9 configuration rather than the d 7 configuration assumed by most previous investigators. The anisotropy of the g values, determined from the electron spin resonance spectra of frozen solutions, varies considerably from complex to complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 6 publications
5
48
0
Order By: Relevance
“…The sample buffer was 25 mM HEPES, 2.5 mM CaCl 2 , 100 mM NaCl, 100 mM NaNO 3 , pH 7.5. B, simulated EPR spectra of persulfide-ligated DNIC (g Ќ ϭ 2.044, g ϭ ϭ 2.032) (31,46) and two thiol-coordinated DNICs at g(ϳ) 2.04 (g Ќ ϭ 2.045, g ϭ ϭ 2.023) (29,44) and g(ϳ) 2.02 (g Ќ ϭ 2.023, g ϭ ϭ 2.016) (11,47) that were used to deconvolute the recorded (74 K) EPR spectra in A. C, EPR spectra for nitrosylated FNR (black lines), together with simulations of the experimental data (R 2 (ϳ) 0.90) (gray lines) obtained by the combination of varying amounts of the spectra shown in B.…”
Section: The [4fe-4s] Cluster Of Fnr Reacts Rapidly With No-the Reactmentioning
confidence: 99%
“…The sample buffer was 25 mM HEPES, 2.5 mM CaCl 2 , 100 mM NaCl, 100 mM NaNO 3 , pH 7.5. B, simulated EPR spectra of persulfide-ligated DNIC (g Ќ ϭ 2.044, g ϭ ϭ 2.032) (31,46) and two thiol-coordinated DNICs at g(ϳ) 2.04 (g Ќ ϭ 2.045, g ϭ ϭ 2.023) (29,44) and g(ϳ) 2.02 (g Ќ ϭ 2.023, g ϭ ϭ 2.016) (11,47) that were used to deconvolute the recorded (74 K) EPR spectra in A. C, EPR spectra for nitrosylated FNR (black lines), together with simulations of the experimental data (R 2 (ϳ) 0.90) (gray lines) obtained by the combination of varying amounts of the spectra shown in B.…”
Section: The [4fe-4s] Cluster Of Fnr Reacts Rapidly With No-the Reactmentioning
confidence: 99%
“…32, 33 Investigations into the structures and physicochemi cal properties of synthetic models of active sites of non heme [Fe-S] nitrosyl proteins are related to application of knowledge in practice for the selective delivery of nitro gen monoxide in vivo. [34][35][36][37][38][39][40][41][42][43][44][45] In recent years, a search for, and studies of, new nitrogen monoxide donors have at tracted considerable attention of experts in practical medi cine. There are several classes of compounds that gener ate nitrogen monoxide during metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…DNICs are paramagnetic (S=1/2) with a characteristic g-value of ≈ 2.03 that is consistent across all ligands. They exhibit distorted tetrahedral geometry and roughly linear Fe-NO bonds, and EPR, IR, and crystallographic structural data are available for a very large range of complexes of this type [84,85]. As described above, DFT calculations combined with spectroscopic observations revealed that that the S=1/2 DNIC, which is represented as {Fe(NO)2} 9 in the Enemark-Feltham notation, is best described by two resonance structures consisting of a high spin Fe 3+ (S= 5/2) antiferromagnetically coupled to two NO -ligands (each S=1), and a high spin Fe 2+ (S=2) antiferromagnetically coupled to an overall quartet 4 (NO)2 -ligand (S=3/2) [76].…”
Section: Iron-nitrosyl Complexesmentioning
confidence: 99%